The impact of applying target costing on enhancing the competitive advantage of industrial companies in the kingdom of Saudi Arabia: A field study - Abdulaziz, Jafar Othman Elsharif; Alharbi, Mohammed Atiah (Edelweiss Applied Science and Technology, 2025)
This study explores the impact of implementing the Target Costing (TC) approach on enhancing the competitive advantage of industrial companies in the Kingdom of Saudi Arabia. The research adopts a descriptive-analytical methodology, utilizing a structured questionnaire distributed to 211 financial managers, accountants, and administrative staff. The collected data were analyzed using SPSS to assess the relationship between TC application and key dimensions of competitiveness, including cost reduction, quality enhancement, and operational flexibility. The findings reveal that applying TC has a statistically significant positive effect on reducing costs, improving product quality, and increasing the ability to innovate and adapt to market changes. These outcomes demonstrate the potential of TC as a strategic tool for strengthening firms’ competitive positioning. The study concludes that TC should be widely adopted across Saudi industrial firms to optimize resource utilization and sustain competitive advantage. Practical implications include the need for management to invest in employee training, adopt modern cost management systems, and align pricing strategies with market expectations.